MiRNAs as Therapeutic Targets in Inflammatory Disease. (November 2019) - Lu, Qianjin; Wu, Ruifang; Zhao, Ming; Garcia-Gomez, Antonio; Ballestar, Esteban
Abstract : In the past decade, we have witnessed considerable developments in understanding the roles and functions of miRNAs. In parallel, the identification of alterations in miRNA expression in inflammatory disease indicates their potential as therapeutic targets. Pharmacological treatments targeting abnormally expressed miRNAs for inflammatory diseases are not yet in clinical practice; however, some small compounds and nucleic acids targeting miRNAs have shown promise in preclinical development. Here, we focus on recent advances in understanding miRNA deregulation in inflammatory diseases and provide an overview of the current development of miRNA-based therapeutics in these diseases with an emphasis on newly discovered miRNA therapeutic targets. Highlights: miRNAs are key regulators of gene expression implicated in a range of biological phenomena and widely dysregulated in inflammatory diseases. miRNAs are highly specific in relation to their direct targets in a cell- and tissue-type manner; however, many dysregulated pathways are shared across different inflammatory diseases. Researchers have now developed various methods and strategies to specifically reverse the dysregulated expression of miRNAs implicated in inflammatory diseases. These methods are mainly based on the sequence complementarity of nucleic acids and are therefore highly specific. Several preclinical studies support the possibility of reverting altered levels of miRNAs in inflammatory diseases, which in turn show the promise of miRNA-based therapeutics for inflammatory conditions in the near future.